Implementasi Otomasi Kandang dalam Rangka Meminimalisir Heat Stress pada Ayam Broiler dengan Metode Fuzzy Sugeno - Abdurrahman Arif Kasim; Rizal Maulana; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
A temperature rise that exceeds the comfort zone leads to heat stress to broiler chickens, where the chicken will experience a decrease in growth, decreased feed, anxiety, increased water consumption and lead to death. The comfortable zone temperature of broiler chickens ranges from 20-25 Â°C, humidity ranges from 50-70%, and ammonia levels from 0-5 PPM whereas the current temperature problem in Indonesia fluctuates between 29-36 Â°C. Based on the problem is made automation system to minimize heat stress with Fuzzy Sugeno method. This study using 3 parameters of temperature, humidity, and ammonia from the readings of DHT11 sensors and MQ 135 sensors as input and output of fan speed and water pump dewy scale on the system. To determine the output using Fuzzy Sugeno method. It can be concluded that this system is able to minimize heat stress with the test conducted for 15 days by using 2250 broiler chickens where the death of chickens in cages that do not use this system the number of deaths as many as 93 chickens, and in cages using this system the number of fewer deaths as many as 42 chickens.